Coping With Information Style, Self‐Concealment, Internalized Stigma, and Family Burden Among Parents of Children With Psychiatric Disorders. Issue 4 (31st January 2021) - Sefi, Shir; Shoval, Gal; Lubbad, Nesrin; Goldzweig, Gil; Hasson‐Ohayon, Ilanit
Abstract : Parents of children with psychiatric disorders who are hospitalized in a psychiatric unit often experience family burden. Family burden has been found to be affected by many variables related to parents' personal traits and ways of reacting to the disorder. The current study examined the association between information coping styles (monitoring and blunting) and family burden, among parents of children who were hospitalized in a day care unit. The possible role of self‐stigma as a mediator between coping style and family burden and the role of self‐concealment as a moderator between coping style and self‐stigma were examined. A total of 41 parents completed questionnaires assessing their levels of self‐stigma, information coping style, self‐concealment, and family burden. Self‐stigma was found to mediate the positive association between the monitoring coping style and family burden. Moreover, a moderation effect of self‐concealment was found, indicating that monitoring parents suffered from higher levels of self‐stigma particularly if they had a high tendency toward self‐concealment. Taking into account parents' information, coping style, self‐stigma, and self‐concealment can help professionals tailor family interventions according to parents' diverse needs. A monitoring coping style may not be beneficial especially when combined with concealment, suggesting the need to promote other coping styles. RESUMEN: Los padres de niños con trastornos psiquiátricos que están internados en una clínica psiquiátrica con frecuencia sufren agobio familiar. Se ha descubierto que el agobio familiar está afectado por muchas variables relacionadas con las características personales de los padres y las maneras de reaccionar al trastorno. En el presente estudio se analizó la asociación entre los estilos de afrontamiento de la información (supervisión y evitación) y el agobio familiar entre padres de niños que estaban internados en un hospital de día. Se examinó el posible rol del autoestigma como mediador entre el estilo de afrontamiento y el agobio familiar, y el rol del autoocultamiento como moderador entre el estilo de afrontamiento y el autoestigma. Un total de 41 padres contestaron cuestionarios donde se evaluaron sus niveles de autoestigma, el estilo de afrontamiento de la información, el autoocultamiento y el agobio familiar. Se descubrió que el autoestigma medió la asociación positiva entre el estilo de afrontamiento de supervisión y el agobio familiar. Además, se descubrió un efecto moderador del autoocultamiento, lo cual indica que los padres supervisores sufrían de niveles más altos de autoestigma, particularmente si tenían una alta tendencia hacia el autoocultamiento. Tener en cuenta el estilo de afrontamiento de la información, el autoestigma y el autoocultamiento de los padres puede ayudar a los profesionales a adaptar las intervenciones familiares de acuerdo con las distintas necesidades de los padres. Es posible que un estilo de afrontamiento de supervisión no sea beneficioso, especialmente si está combinado con el ocultamiento, lo cual sugiere la necesidad de promover otros estilos de afrontamiento. 摘要: 在精神科接受住院治疗的有精神障碍儿童其父母们往往承受着家庭负担。研究已经发现家庭负担受许多变量的影响, 这些变量与父母的个人性格特征和对精神病患的反应方式等相关。本研究调查了日托所住院儿童的父母其信息应对方式(监督型和钝化型)与家庭负担之间的关系。本研究考察了自我苛责在应对方式与家庭负担之间的调节作用, 以及自我隐瞒在应对方式与自我苛责之间的调节作用。本研究对41名家长进行自责内疚、信息应对方式、自我隐瞒和家庭负担方面的问卷调查。自我耻辱感在监督型的应对方式与家庭负担之间有调节作用。此外, 研究还发现了自我隐瞒有调节作用, 这表明父母对自己的苛责和内疚的程度比较高, 特别是当他们有较高的自我隐瞒倾向时。把父母的信息应对方式、自责内疚和自我隐藏这些方面考虑进去, 有助于专业人员根据父母的不同需求进行针对性的家庭干预。监督型的应对方式可能并不能产生有益的结果, 特别是当与自我隐藏相结合时, 这正表明有必要促进其他类型的应对方式。